Displacement and equilibrium mesh-free formulation based on integrated radial basis functions for dual yield design. (October 2016) - Ho, Phuc L.H.; Le, Canh V.; Tran-Cong, T.
Abstract: This paper presents displacement and equilibrium mesh-free formulation based on integrated radial basis functions (iRBF) for upper and lower bound yield design problems. In these approaches, displacement and stress fields are approximated by the integrated radial basis functions, and the equilibrium equations and boundary conditions are imposed directly at the collocation points. In this paper it has been shown that direct nodal integration of the iRBF approximation can prevent volumetric locking in the kinematic formulation, and instability problems can also be avoided. Moreover, with the use of the collocation method in the static problem, equilibrium equations and yield conditions only need to be enforced at the nodes, leading to the reduction in computational cost. The mean value of the approximated upper and lower bound is found to be in excellent agreement with the available analytical solution, and can be considered as the actual collapse load multiplier for most practical engineering problems, for which exact solution is unknown.